Eco-Immunology 2014
DOI: 10.1007/978-94-017-8712-3_1
|View full text |Cite
|
Sign up to set email alerts
|

From Immunology to Eco-Immunology: More than a New Name

Abstract: Eco-immunology recognises that immune systems and responses are an integrated part of an animal's physiology, preventing harm that might be caused by pathogens. Laboratory-based immunology has given a tremendously strong understanding of the mechanisms by which this system functions, though this is focused on a few species. It is clear that immune responses are costly to make, such that animals have difficult decisions of resource allocation to make. For this reason alone, an eco-immunological approach is key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 73 publications
0
26
0
Order By: Relevance
“…Vertebrates' gastrointestinal (GI) tract is a composite microbial ecosystem housing a complex and dynamic consortium of microorganisms, which play critical roles in the nutrition and health of the host (Brugman & Nieuwenhuis 2010;Cerf-Bensussan & Gaboriau-Routhiau 2010;Viney & Riley 2014). In animal GI micro-ecosystem, there are complex and relatively stable microbial-microbial and hostmicrobial relationships (Hooper & Gordon 2001;Ley et al 2006;P erez et al 2010;Mazmanian & Lee 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Vertebrates' gastrointestinal (GI) tract is a composite microbial ecosystem housing a complex and dynamic consortium of microorganisms, which play critical roles in the nutrition and health of the host (Brugman & Nieuwenhuis 2010;Cerf-Bensussan & Gaboriau-Routhiau 2010;Viney & Riley 2014). In animal GI micro-ecosystem, there are complex and relatively stable microbial-microbial and hostmicrobial relationships (Hooper & Gordon 2001;Ley et al 2006;P erez et al 2010;Mazmanian & Lee 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Information on fish gut microbiota is generally useful for understanding the factors that affect fish health, as research has shown that the gut microbiota play a key role in the health and nutrition of the host [25][26][27]. Fish gut microbiota contribute to digestion and can affect growth, reproduction, overall population dynamics, and the vulnerability of the host fish to disease [28].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, research has shown that the gut microbiota play a key role in the health and nutrition of the host [5][6][7] . Fish gut microbiota contribute to digestion and can affect growth, reproduction, overall population dynamics and the vulnerability of the host fish to disease 8 .…”
mentioning
confidence: 99%